2020
DOI: 10.1002/rra.3671
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the turbulent flow behaviour through partially distributed discontinuous rigid vegetation in an open channel

Abstract: Riparian vegetation does not only affect the channel flow carrying capacity, but also plays significant roles in water management, stream restoration, and river rehabilitation. This study numerically investigates the flow characteristics through longitudinally discontinuous rigid vegetation occupying half width of the channel, with the help of three-dimensional software FLUENT in which a Reynolds stress turbulence model was adopted. Three varying conditions of vegetation were considered comprising of verticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 48 publications
(81 reference statements)
8
7
0
Order By: Relevance
“…For the simulated vegetation, since the object of this study is the combined vegetation patches of different stem thicknesses, and the vegetation stems are usually cylindrical, so this study uses cylinders with different diameters to simulate vegetation. In addition, in order to enhance the simulation and experimental effects and improve the efficiency, most of the current studies also generalize the whole plant to an effective water blocking cylinder ( Zhao and Huai, 2016 ; Anjum and Tanaka, 2020 ; Wang et al., 2021 ). In this study, a cylinder with a height of h v of 0.08 m was used to simulate open channel vegetation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the simulated vegetation, since the object of this study is the combined vegetation patches of different stem thicknesses, and the vegetation stems are usually cylindrical, so this study uses cylinders with different diameters to simulate vegetation. In addition, in order to enhance the simulation and experimental effects and improve the efficiency, most of the current studies also generalize the whole plant to an effective water blocking cylinder ( Zhao and Huai, 2016 ; Anjum and Tanaka, 2020 ; Wang et al., 2021 ). In this study, a cylinder with a height of h v of 0.08 m was used to simulate open channel vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Kazem et al (2021a); Kazem et al (2021b) studied the vortex structure in the channel of vegetation patch and the characteristics of turbulence gradually subsiding in the undeveloped area downstream of the patch by changing the patch size, and its research results showed that the presence of patches has a great influence on the flow structure inside and around the patches, and there are three different flow layers downstream of vegetation patches: wake layer, mixed layer and shear layer. However, studies on the patch distribution of partially discontinuous vegetation on open channel flow is not systematic enough, although this vegetation distribution pattern is more common in natural channels (Anjum and Tanaka, 2020;Li et al, 2020). In addition, most current studies use the uniform size of vegetation for generalized simulation processing, which does not conform to the natural situation of river vegetation (Sand Jensen and Madsen, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Anjum and Tanaka [25] used the k − ϵ model to elucidate the flow structure through discontinuous vertically layered vegetation that had been covered the channel's entire width.Large eddy simulation (LES) model was also applied by Huai et al [26] to simulate turbulent flow in a partially vegetated open channel. Anjum et al [27] investigated turbulent flow behavior in an open channel with partially dispersed discontinuous stiff vegetation. They found that the velocity in plant patches was lower than that in the non-vegetated zone due to plant resistance, which affected channel carrying capacity.…”
Section: Introductionmentioning
confidence: 99%
“…An array of porous vegetation patches with patch‐to‐patch interactions, such as reeds, is common in rivers but has not been adequately investigated. Few studies have investigated the effect of patchy vegetation on flow structures (Anjum & Tanaka, 2020; Ghani, Anjum, Pasha, & Ahmad, 2019). Providing accurate predictions about the depth‐averaged streamwise velocity profiles in the flow with an array of discontinuous vegetation patches remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…An array of porous vegetation patches with patch-topatch interactions, such as reeds, is common in rivers but has not been adequately investigated. Few studies have investigated the effect of patchy vegetation on flow structures (Anjum & Tanaka, 2020;Ghani, Anjum, Pasha, & Ahmad, 2019)…”
mentioning
confidence: 99%